Peranan Pendidikan Agama Kristen Dalam Keluarga Sebagai Restorasi Terhadap Perilaku Remaja Kristen Masa Kini - Viktor Deni Siregar; Ester Debora br Siburian; Elfrida Elena Br Silaban; Sinta Tiarnauli Siburian; Yunira Nababan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
Teenagers as the future generation of the church and nation must be given proper attention and education so that their behavior is in accordance with existing norms. Christian Religious Education in the family is the most important education to teach how the person of God is with Humans. Christian Religious Education cannot be limited by space and time because it is very flexible and can be done anywhere. The role given by Christian Religious Education itself, of course, must provide teaching about the realities of life so that adolescents are able to have an understanding of their life goals. Christian Religious Education is role includes in the family to provide good behavior in the present, namely; Family behavioral education center, setting an example, restoration, family place of worship. This research was conducted using a qualitative descriptive literature method, by collecting studies related to research conducted either through books, proceedings, national and international journals. Then do the analysis, provide arguments and find the results of the study. The purpose of the research was conducted so that today's Christian youth have better behavior through Christian Religious Education in the Family and so that Christian youth do not deviate from the person of Jesus himself as a perfect person in all respects.